The SDR and Its Potential as an International Reserve Asset - Chelsky, Jeff (World Bank, Washington, DC, 2012)
Since the onset of the global financial crisis, there has been an upswing of interest among some prominent policy makers and academics in the International Monetary Fund's (IMF) Special Drawing Right (SDR) as a 'safe' international reserve asset. But preexisting constraints on the SDR and the magnitude of support required to push through the reforms necessary to enhance the SDR's role make it unlikely that ambitious aspirations for this 'quasi-currency' will be realized. Moreover, the case for enhancing the SDR's role has been somewhat overstated, as has the view that the current international monetary system requires the dominance of a single currency, namely the U.S. dollar. To a significant extent, U.S. dollar dominance is the result of specific policy choices by individual countries (for example, export-led growth strategies, close links to the U.S. dollar) rather than an inherent rigidity in the international monetary system. Many of the problems that some policy makers are seeking to address through a greater role for the SDR can more easily be achieved in the context of the continuing trend to a multicurrency reserve system.